Exposure to persistent organic pollutants and sperm DNA methylation changes in Arctic and European populations. (23rd January 2016) - Consales, Claudia; Toft, Gunnar; Leter, Giorgio; Bonde, Jens Peter E.; Uccelli, Raffaella; Pacchierotti, Francesca; Eleuteri, Patrizia; Jönsson, Bo A.G.; Giwercman, Aleksander; Pedersen, Henning S.; Struciński, Paweł; Góralczyk, Katarzyna; et al.
Abstract : Persistent organic pollutants (POPs), such as PCBs (polychlorinated biphenyls) and DDT [1, 1, 1‐trichloro‐2, 2‐bis(4‐chlorophenyl)ethane], are environmental contaminants with potential endocrine disrupting activity. DNA methylation levels in peripheral blood lymphocytes have been associated with serum concentrations of POPs in Greenland Inuit and Korean populations. Greenland Inuits are characterized by the highest worldwide POP levels. In this cross‐sectional study we evaluated the relationship between serum POP concentrations and DNA methylation levels in sperm of non‐occupationally exposed fertile men from Greenland, Warsaw (Poland), and Kharkiv (Ukraine). Serum levels of PCB‐153 [1, 2, 4‐trichloro‐5‐(2, 4, 5‐trichlorophenyl)benzene], as a proxy of the total PCBs body burden, and of p, p '‐DDE [1, 1‐dichloro‐2, 2‐bis(4‐chlorophenyl)ethylene], the main metabolite of DDT were measured. Sperm DNA methylation level was assessed globally by flow cytometric (FCM) immunodetection of 5‐methyl‐cytosines and at specific repetitive DNA sequences (Alu, LINE‐1, Satα) by PCR‐pyrosequencing after bisulfite conversion. Multivariate linear regression analysis was applied to investigate correlations between serum POP concentrations and DNA methylation. No consistent associations between exposure to POPs and sperm DNA methylation at repetitive DNA sequences were detected. A statistically significant global decrease in methylation was associated with exposure to either POP by FCM analysis. This is the first study to investigate environmental exposure to POPs and DNA methylation levels considering sperm as the target cells. Although POP exposure appears to have a limited negative impact on sperm DNA methylation levels in adult males, the global hypomethylation detected by one of the methods applied suggests that further investigation is warranted. Environ. Mol. Mutagen. 57:200–209, 2016. © 2016 Wiley Periodicals, Inc.